Performance of anode materials in electro-Fenton oxidation of cefoperazone in chloride medium: New insight into simultaneous mineralization and toxic byproducts formation. (1st December 2022) - Wen, Zhenjun; Ren, Songyu; Zhang, Yanyu; Li, Jiuyi; Zhang, Zhongguo; Wang, Aimin
Abstract: Electrochemical oxidation of saline organic wastewater is always accompanied by the formations of toxic chlorinated byproducts, hence it is of great significance to control the potential toxic effect while ensuring the mineralization efficiency. In this study, the electro-Fenton (EF) degradation of 200 mg L −1 cefoperazone (CFPZ) has been investigated in chloride media, performed in 0–20 mM NaCl as well as 50 mM Na2 SO4 comparatively. An active carbon fiber (ACF ) was used as cathode, while an active RuO2 /Ti, non-active SnO2 –Sb2 O5 /Ti or boron-doped diamond supported on niobium (BDD/Nb) was selected as anode. In EF process, along with active chlorine originated from the anodic oxidation of Cl −, CFPZ decays always been promoted, but the mineralization extents got inhibited. Both the mineralization and the chlorinated byproducts formation increased in sequence of RuO2 /Ti < SnO2 –Sb2 O5 /Ti < BDD/Nb. Chlorinated byproducts were largely recalcitrant when RuO2 /Ti or SnO2 –Sb2 O5 /Ti anodes were used, leading to only a small portion of Cl − being converted to active chlorine and chlorate (ClO3 − ). When using BDD/Nb, Cl − was further oxidized to ClO3 − and, mostly, to perchlorate (ClO4 − ), due to the action of the largely generated hydroxyl radical ( OH) and physically adsorbed OH (BDD( OH)). This behavior demonstrated the toxic risk could be limited by choosing an adequate anode. The evolutions of active chlorine, Cl −, ClO3 −, ClO4 −, NH4 + and NO3 − were determined to clarify the behavior of electrodes in EF process. Nine aromatic intermediates and eleven volatile intermediates were detected by liquid and/or gas chromatography mass spectrometry respectively, meanwhile four carboxylic acids (oxalic, oxamic, formic and fumaric acids) were quantified as final byproducts, allowing the proposal of a plausible pathway of CFPZ mineralization in Cl − -containing medium. Graphical abstract: Image 1 Highlights: Role of anode materials in cefoperazone degradation in chloride media was studied. High mineralization and low ClO3 − /ClO4 − formation achieved in the SnO2 –Sb2 O5 /Ti-EF. Higher ClO3 − /ClO4 − accumulation at the BDD/Nb anode constitutes a major drawback. A plausible CFPZ degradation pathway in chloride medium in EF process was proposed.